Faster and less invasive tools to identify patients with ileal colonization by adherent‐invasive E. coli in Crohn's disease. Issue 9 (17th November 2021) - Buisson, Anthony; Vazeille, Emilie; Fumery, Mathurin; Pariente, Benjamin; Nancey, Stéphane; Seksik, Philippe; Peyrin‐Biroulet, Laurent; Allez, Matthieu; Ballet, Nathalie; Filippi, Jérôme; Yzet, Clara; Nachury, Maria; et al.
Abstract: Background and Aims: The identification of Crohn's disease (CD)‐associated adherent and invasive Escherichia coli (AIEC) is time‐consuming and requires ileal biopsies. We aimed to identify a faster and less invasive methods to detect ileal colonization by AIEC in CD patients. Methods: CD patients requiring ileo‐colonoscopy were consecutively enrolled in this prospective multicenter study. Samples from saliva, serum, stools, and ileal biopsies of CD patients were collected. Results: Among 102 CD patients, the prevalence of AIEC on ileal biopsies was 24.5%. The abundance and global invasive ability of ileal‐associated total E. coli were respectively ten‐fold ( p = 0.0065) and two‐fold ( p = 0.0007) higher in AIEC‐positive (vs. AIEC‐negative), while abundance of total E. coli in the feces was not correlated with AIEC status in the ileum. The best threshold of ileal total E. coli was 60 cfu/biopsy to detect AIEC‐positive patients, with high negative predictive value (NPV) (94.1%[80.3–99.3]), while the global invasive ability (>9000 internalized bacteria) was able to detect the presence of AIEC with high positive predictive value (80.0% [55.2–100.0]). Overall, 78.1% of the AIEC + patients were colonized by two or less different AIEC strains. The level of serum anti‐total E. coli antibodies (AEcAb) was higher in AIEC‐positive patients ( p = 0.038) with a very high negative predictive value (96.6% [89.9–100.0]) ( p = 0.038) for a cut‐off value > 1.9 × 10 −3 . Conclusions: More than two thirds of AIEC‐positive CD patients were colonized by two or less AIEC strains. While stools samples are not accurate to screen AIEC status, the AEcAb level appears to be an attractive, rapid and easier biomarker to identify patients with Crohn's disease harboring AIEC.